Characteristics of bubble rise in a liquid - Tan, Si Ying (Nanyang Technological University, 2022)
The study of bubble dynamics has been an active area of research. Extensive experimental and numerical research has been conducted to investigate the rising motion of a single bubble. Many studies have concluded that bubbles reach terminal velocity which greatly simplifies the calculations of a de-aeration chamber design for minimising attrition. This experimental study aimed to reaffirm that bubbles reach terminal velocity and to extend past studies by examining a wider range of bubbles with varying sizes from approximately 5 mm to 20 mm in diameter and in fluid mediums of varying viscosities – glycerol and aqueous glycerol solution. The study examined the bubble shape, size and trajectory during ascension, as well as the effects of fluid viscosity, bubble velocity and aspect ratio on drag coefficient and Reynolds number. The experimental results concluded that bubbles can reach terminal velocity after rising approximately 40 mm and the terminal rise velocity is highly correlated to the mean bubble width when ascending in higher viscosity fluids. Simultaneously, the trajectory and the bubble shape, in terms of aspect ratio, are observed to be highly dependent on both bubble size and fluid viscosity, which affects the components of a drag force. Slight deviations from the standard drag coefficient curve for a solid sphere could be due to the differences in aspect ratio which affect the bubble frontal area given that the bubble volume remains constant.